2002
DOI: 10.1007/s11864-002-0038-8
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma is usually present as locally advanced (stage III or IV) disease. Before 1980, the primary treatment was radiotherapy. The 5-year survival rate of patients with stage IVM0 across the world was less than 30%. Local, regional, and systemic recurrences are high in these patients and contributed to the poor survival. Sequential chemotherapy followed by radiotherapy (especially with the combination of cisplatin and 5-fluorouracil infusion for three courses) resulted in a 5-year survival rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…When external beam radiation is the chosen treatment modality for oral carcinoma with N0 neck, National Comprehensive Cancer Network (NCCN) has recommended a total dose of 70Gy to primary tumor and ≤ 50Gy to the neck at risk of occult metastasis. Both chemotherapy and radiotherapy may be associated with complications and this may be more marked in instances of poor pre-treatment evaluation and preparation [2,5,9,19].…”
Section: Discussionmentioning
confidence: 99%
“…When external beam radiation is the chosen treatment modality for oral carcinoma with N0 neck, National Comprehensive Cancer Network (NCCN) has recommended a total dose of 70Gy to primary tumor and ≤ 50Gy to the neck at risk of occult metastasis. Both chemotherapy and radiotherapy may be associated with complications and this may be more marked in instances of poor pre-treatment evaluation and preparation [2,5,9,19].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy is often performed in patients with unresectable cancer or patients in whom surgery is considered difficult because of older age or comorbidities. However, since 1992, the efficacy of CRT has been well documented, and CRT has been clearly shown to improve cure rates compared with radiotherapy alone [1,2,[5][6][7][8][9]. Currently, the guidelines of the National Comprehensive Cancer Network recommend CRT for esophageal cancer such as medically unfit for surgery or surgery not elected case [3].…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent chemoradiotherapy (CRT) has been reported to significantly increase the survival rate of patients with esophageal cancer as compared with radiation therapy alone [1,2]. CRT is proposed to be the standard treatment for advanced esophageal cancer [3].…”
Section: Introductionmentioning
confidence: 99%
“…1 Currently, the primary medical management for NPC is radiotherapy, while chemotherapy and surgery (eg, nasopharyngectomy) are elective treatments. 2 Although previous research has shown that these aggressive treatment methods can successfully control tumors and thus increase overall survival rates, 1 survivors generally experience many associated side effects, such as neck muscle fibrosis, 3,4 trismus or restricted mouth opening, 5,6 and shoulder dysfunctions. 7 The disease can also directly cause chronic symptoms, such as pain and fatigue.…”
Section: Introductionmentioning
confidence: 99%